Optimization of culture conditions for the production, antifungal activity and characterization of secondary metabolites of Trichoderma longibrachiatum - PRIYA, R.; BALACHANDAR, S.; PRABHAKARAN, N. (Journal of Biological Control, 2023)
The present study was intended to optimize the culture conditions for secondary metabolite production by endophytic fungi. Based on the morphology and phylogeny, the fungus was identified as Trichoderma longibrachiatum isolated from brinjal leaf based on morphological characterization. The antifungal activity was evaluated against phytopathogens such as Macrophomina phaseolina, Phytopthora infestans, Colletotrichum falcatum and Colletotrichum gloeosporioides through the overlapping method, culture filtrate and organic fraction from Potato dextrose both as a growth medium. The organic fraction exhibited a significant antifungal activity, while modifications in medium composition may possess a major impact on the quantity and quality of secondary metabolites production. To achieve maximum metabolite production, the growth of the culture was optimized with screening of basal media, carbon, nitrogen, pH, trace elements and incubation period. The final optimized fermentation conditions were Minimal ereavis broth as basal media; glucose and sucrose as carbon source; Peptone and Yeast extract as nitrogen source, sodium nitrate as precursor; pH as 6; and incubation period as 7 days at 28°C. This optimization resulted in antifungal activity of 47.19-60.67% against M. phaseolina, P. infestans, C. falcatum, and C. gloeosporioides which was higher than that before optimization (43.80%). GCMS revealed distinct metabolites of T. longibrachiatum, comprising antifungal metabolites and molecules with additional bioactivities. These results strengthen ongoing research on disease control in agriculture by emphasizing the biocontrol potential of T. longibrachiatum isolated from brinjal phyllosphere against plant pathogenic fungi.